2020
DOI: 10.3390/genes11030322
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genic SSRs Provide a Perspective for Studying Environmental Adaptation in the Endemic Shrub Tetraena mongolica

Abstract: Tetraena mongolica is a xerophytic shrub endemic to desert regions in Inner Mongolia. This species has evolved distinct survival strategies that allow it to adapt to hyper-drought and heterogeneous habitats. Simple sequence repeats (SSRs) may provide a molecular basis in plants for fast adaptation to environmental change. Thus, identifying SSRs and their possible effects on gene behavior has the potential to provide valuable information for studies of adaptation. In this study, we sequenced six individual tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We also found that the microsatellites located in CDS regions were dominated by tri-nucleotides, while other SSR motifs accounted for a small proportion. This was common in many plants, such as Phoenix dactylifera L. (Zhao et al, 2013), Tetraena mongolica (Dang et al, 2020), and Paeonia lactiflora (Wan et al, 2020). Compared to other repeat types, tri-nucleotide is less likely to frame-shift mutations in coding regions (Metzgar et al, 2000).…”
Section: Microsatellite Distribution In Different Genic Regionsmentioning
confidence: 99%
“…We also found that the microsatellites located in CDS regions were dominated by tri-nucleotides, while other SSR motifs accounted for a small proportion. This was common in many plants, such as Phoenix dactylifera L. (Zhao et al, 2013), Tetraena mongolica (Dang et al, 2020), and Paeonia lactiflora (Wan et al, 2020). Compared to other repeat types, tri-nucleotide is less likely to frame-shift mutations in coding regions (Metzgar et al, 2000).…”
Section: Microsatellite Distribution In Different Genic Regionsmentioning
confidence: 99%
“…It was previously suggested that SSRs in plants may play a role in fast adaptation to environmental changes [ 26 ]. In general, Ophioglossaceae and ferns are known to have large genomes.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the observed phenotypic changes, GO ( ) (accessed on 2 April 2022) and KEGG ( ) (accessed on 2 April 2022) enrichment analyses of annotated DEGs were performed using Phyper ( ) (accessed on 10 April 2022) based on the hypergeometric test [ 71 ]. The significance levels of terms and pathways were subjected to Bonferroni correction based on the Q-value with a rigorous threshold (Q-value ≤ 0.05).…”
Section: Methodsmentioning
confidence: 99%